Pengaruh Struktur Modal, Likuiditas dan Pertumbuhan Penjualan Terhadap Kinerja Keuangan - Yuliani, Eva (Jurnal Ilmu Manajemen, 2021)
This study aims to determine the effect of the effect of capital structure, liquidity and sales growth on the financial performance of food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange. This research uses quantitative research. The sampling technique used in this research is purposive sampling. The research sample obtained 60 observational data. The method used is multiple linear regression analysis. The results of this study indicate that the Capital Structure (DER), Liquidity (CR), and Sales Growth (SG) have a simultaneous effect on financial performance (ROA). Partially the capital structure variable (DER) has a significant effect on financial performance (ROA), the liquidity variable (CR) partially has a significant effect on financial performance (ROA) and the Sales Growth variable (SG) has a significant effect on financial performance (ROA). Investors can pay attention to capital structure, liquidity, sales growth because the results of this study indicate that these variables have an effect on high financial performance which can later be profitable for a company